2012
DOI: 10.1038/ncomms2276
|View full text |Cite
|
Sign up to set email alerts
|

Elevated oncofoetal miR-17-5p expression regulates colorectal cancer progression by repressing its target gene P130

Abstract: MicroRNAs (miRNAs) are essential for regulating normal embryonic development and carcinogenesis. Here we report that miR-17-5p, an oncofoetal miRNA, is a key regulator of colorectal cancer progression. We show that miR-17-5p is an oncogenic miRNA that regulates tumorigenesis and progression by targeting the gene encoding P130 and subsequently activating the Wnt/b-catenin pathway. Using specimens from two large cohorts of colorectal cancer patients, we found that patients whose tumours had high miR-17-5p expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 25 publications
4
101
1
3
Order By: Relevance
“…In the recent study, miR-203 has significantly low expression in cancer tissues compared to non-tumor counterparts (Viticchiè et al, 2011;Takeshita et al, 2012;Gu et al, 2013), while there were up-regulation of miR-203 was observed in pancreatic adenocarcinomas and breast, cancers (Naoki et al, 2010;Madhavan et al, 2012), we think the differential expression of miRNAs may be the result of tissue-specific differences. Just as Baffa et al suggested (Baffa et al, 2009).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the recent study, miR-203 has significantly low expression in cancer tissues compared to non-tumor counterparts (Viticchiè et al, 2011;Takeshita et al, 2012;Gu et al, 2013), while there were up-regulation of miR-203 was observed in pancreatic adenocarcinomas and breast, cancers (Naoki et al, 2010;Madhavan et al, 2012), we think the differential expression of miRNAs may be the result of tissue-specific differences. Just as Baffa et al suggested (Baffa et al, 2009).…”
Section: Discussionmentioning
confidence: 82%
“…Numerous of studies have shown that alterations in miRNAs synthesis in human cancers are often related to tumor development, progression and metastasis. There is a hypothesis that deregulated synthesis of miRNAs, which in turn regulate protein synthesis, is one of the most important factors contributing to cancer development (Lin et al, 2012;Ma et al, 2012;Liang et al, 2013). Altered miRNA expression profiles have also been reported in cervical cancer as compared with normal cervix (Lee et al, 2008;Hu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor tissue miR‐17‐5p high expression is illustrated to correlate with worse OS in nasopharyngeal carcinoma patients and colorectal cancer patients, and is an independent risk factor for DFS and OS in hepatocellular carcinoma patients 33, 35, 60. And tumor tissue miR‐18a high expression correlates with unfavorable OS in ovarian cancer patients and hepatocellular carcinoma patients 61, 62.…”
Section: Discussionmentioning
confidence: 97%
“…MiR‐17‐5p, belonging to the miR‐17‐92 cluster, has been found to be upregulated in various cancer tissues and correlated with advanced disease conditions including colorectal cancer, human breast cancer, lung cancer, pancreatic cancer, and so on, which promotes tumorigenesis, cancer cells proliferation, migration, and invasion via regulating P130, HMG box‐containing protein 1, TGFβ‐2 receptors, and other cancer‐related genes 34, 35, 36, 37. MiR‐18a, another pro‐angiogenic miRNA, is also discovered to be increased in several cancers including breast cancer, esophageal squamous cell carcinoma, and colorectal carcinoma, and it induces cancer cells’ proliferation, invasion, and autophagy through regulating PTEN‐PI3K‐AKT‐mTOR signaling axis and Dicer 32, 38, 39.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of constitutively active β-catenin may result in colorectal tumourigenesis (27). Through in vitro and in vivo experiments, Ma et al proved that miRNA-17-92 increases the expression of β-catenin indirectly by targeting P130, and subsequently promotes the tumourigenesis and progression of CRC (28). Strillacci et al revealed that miR-101 regulates Wnt/β-catenin signalling in CRC through the strong impairment of β-catenin nuclear accumulation and β-catenin-driven transcriptional activity, following the control of downstream target gene expression and malignant phenotype in cancer cells (29).…”
Section: Function Of Mirnas In Crcmentioning
confidence: 99%